Heart Failure in Infancy and Childhood - Dan G. McNamara (Indonesian Pediatric Society, 1976)
Recognition of heart failure, especially left heart failure is often more difficult in the infant than the medical management. Treatment of failure is aimed at: Rapid relief of congestion in vital organs such as the lung and Improving the oxygen supply to deprived organs. Basically the plan should be aimed at increasing cardiac output, decreasing circulating blood volume and preventing conditions which call for increased oxygen utilization. For patients with pulmonary edema attention is directed at improving ventilation as much as in improving cardiac output. Heart failure in the infant may now be treated with greater optimism and hope than was justified ten years ago. Some infants recover entirely with no further treatment needed while others recover sufficiently to reach the cardiovascular surgeon in a reasonable state for definitive surgical repair.